Послідовний аналіз якості продукції - Ащепкова, Наталія Сергіївна; Богданов, В'ячеслав Олександрович (НТУ "ХПІ", 2016)
Представлено результати експериментального дослідження системи керування якістю продукції зі спіненого полістиролу. Визначено статистичні параметри вибірки для прийняття рішення про відповідність партії виробів стандартам якості. Представлено результати чисельного рішення задачи послідовного аналізу якості продукції з використанням Mathcad. Застосування розробленого програмного забезпечення дозволяє по початкових даних здійснити перевірку гіпотез, визначити мінімальний обсяг партії перевіряємих виробів, визначити сумарну кількість дефектних виробів, оперативну характеристику L(p) та функцію середнього числа спостережень за критерієм Е(р).

This article discusses the development of quality control system for foamed polystyrene products. An important factor is the significant quality dependence of the finished product on careful implementation of all requirements of the technology, because even the slightest dryness of polystyrene foam can cause rejection of the entire batch of products. The aim of the article is the use of statistical methods for quality control. Statistical sampling parameters to decision-making for compliance of batch of products to quality standards are determined using tabular and graphical method of sequential analysis. To ensure product quality manufacturing process includes the quality control of raw materials; control of multicomponent system parameters "temperature-pressure" in the foam maker; time exposure control in silos and quality control of the finished product. Technical controls of product quality use selective ultrasound diagnosis and photography of end surfaces of the products.
The consecutive analysis of production quality
Keywords: вибірка; гіпотеза; імовірність; критична область; допустимий ризик; метод послідовного аналізу; sampling; hypothesis; decision-making; critical region; allowable risk